Dimethyl 2‐Methylglutarate (Iris): A Green Platform for Efficient Liquid‐Phase Exfoliation of 2D Materials. (30th August 2022) - D'Olimpio, Gianluca; Occhiuzzi, Jessica; Lozzi, Luca; Ottaviano, Luca; Politano, Antonio
Abstract: Liquid‐phase exfoliation of bulk crystals of layered materials, held together by weak interlayer van der Waals forces, is an ideal platform for scalable synthesis of nanosheets. However, it is mandatory to substitute existing solvents, regrettably displaying severe limitations due to toxicity. Here, dimethyl 2‐methylglutarate (Rhodiasolv Iris) is validated for efficient liquid‐phase exfoliation of selected van der Waals materials, namely, MoS2, WS2, GeSe, and graphite. Here, we show that Iris‐assisted liquid phase exfoliation provides high yield (up to 52%) of flakes of 2D materials with aspect ratio as high as 500. Considering the various advantages of Iris over the state‐of‐the‐art solvents, including the absence of toxicity and its biodegradability, this work opens new possibilities for the ecofriendly production of 2D materials and for their extensive usage in industrial processes hitherto semi‐unexplored, owing to the toxicity of state‐of‐the‐art solvents (including the production of drinkable water or fruit juice concentration). Accordingly, the validation of Iris for sustainable liquid‐phase exfoliation of van der Waals crystals has intrinsic outstanding potential commercial impact. Moreover, here the values of the surface tension, Hansen solubility parameter, and viscosity of Rhodiasolv Iris are reported for the first time, which will be relevant also for any other sustainable process based on this new green solvent. Abstract : Here, dimethyl 2‐methylglutarate (Rhodiasolv Iris) is validated as a suitable green solvent for efficient liquid‐phase exfoliation of van der Waals materials. Due to the absence of toxicity and its biodegradability, Iris enables the extensive exploitation of 2D materials in industrial processes, such as the production of drinkable water or fruit juice concentration.